2011
DOI: 10.1158/1055-9965.epi-11-0110
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Cutaneous Squamous Cell Carcinoma and Betapapillomavirus Seropositivity: a Cohort Study

Abstract: Background: It is currently unclear whether betapapillomaviruses (betaPV) play a role in the etiology of cutaneous squamous cell carcinoma (SCC). We investigated the association between betaPV antibodies and subsequent SCC in a population-based cohort study.Methods: Serum samples were collected in 1992 and/or 1996 from 1,311 participants of the communitybased Nambour Skin Cancer Study. These were tested for the presence of L1 antibodies against 21 different betaPV types. Histologically diagnosed SCCs were asce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…24). The presence or absence of individual betaPV types was determined with the skin (beta) PV prototype research assay (Diassay BV), which combines PCR detection and a reverse hybridization assay for typing of 25 genotypes (i.e., HPV types 5,8,9,12,14,15,17,19,20,21,22,23,24,25,36,37,38,47,49,75,76,80,92,93, and 96) as described previously (25). Samples from ICP from Queensland, Australia and OTR from Netherlands were analyzed at the Department of Medical Microbiology of the Leiden University Medical Center (Leiden, The Netherlands).…”
Section: Data and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…24). The presence or absence of individual betaPV types was determined with the skin (beta) PV prototype research assay (Diassay BV), which combines PCR detection and a reverse hybridization assay for typing of 25 genotypes (i.e., HPV types 5,8,9,12,14,15,17,19,20,21,22,23,24,25,36,37,38,47,49,75,76,80,92,93, and 96) as described previously (25). Samples from ICP from Queensland, Australia and OTR from Netherlands were analyzed at the Department of Medical Microbiology of the Leiden University Medical Center (Leiden, The Netherlands).…”
Section: Data and Sample Collectionmentioning
confidence: 99%
“…HPV antibodies, present in about half of those who have evidence of eyebrow hair infection, have been associated with SCC risk in several case-control studies (12)(13)(14)(15)(16), possibly indicating the presence of more active virus. However, it is also possible that presence of skin cancer causes the generation of HPV antibodies and that reverse causality is responsible for this finding (17). An attempt to highlight biologically relevant betaPV infections by looking for betaPV DNA and antibody directed against the same type identified a significant association between SCCs and the concordant detection of antibodies and DNA for at least one betaPV type but no association with antibodies without concordant DNA (7).…”
Section: Introductionmentioning
confidence: 99%
“…The group of studies that "only collected sero-prevalence of B-HPV" was the largest, with nine studies accounting for 1,707 cSCC cases and 3,837 controls/cohort [18][19][20][21][22][23][24][25][26] This category included 6 case-control studies and the highest number of cohort studies (3 out of a total of 4 cohort studies) which highlights the importance of serology as a cost-effective, noninvasive and easily reproducible procedure on large population.…”
Section: Hpv Detection Methodsmentioning
confidence: 99%
“…According to the above detailed results we can clearly see that this review is another proof that an association between B-HPV and cSCC exists in healthy individuals as evidenced by most of the conducted research. There remain a few exceptions consisting of 2 studies that according to their authors had a limited sample size to power a definitive answer regarding this association [21,24].…”
Section: Andersson Et Al [25]mentioning
confidence: 99%
“…22 In addition to reports focused on the correlation between b-PV DNA and disease, numerous seroepidemiological studies have also contributed data suggesting an association between b-PV infection and NMSC or its precursors. [23][24][25][26] Considering a causal function of b-HPV in cancer formation, several studies have identified different transformation mechanisms that may explain a viral contribution to carcinogenesis. High-risk genital HPV types are known to degrade p53, thereby blocking downstream pathways such as apoptosis.…”
Section: Introductionmentioning
confidence: 99%